The Engagement Rate of the Instagram Account @perpustakaanumumkabupatensolok at the Solok Regency Public Library - Gita Tria Afnella; Gustina Erlianti (Darul Yasin Al Sys, 2026)
The increasing use of Instagram as a promotional and communication platform has created new opportunities for public libraries to strengthen audience engagement; however, empirical evidence on engagement performance among regency-level public libraries remains limited. This study analyzes the engagement rate of the Instagram account @perpustakaanumumkabupatensolok, managed by the Solok Regency Public Library. A quantitative descriptive design was employed to examine 114 posts published from September to December 2025 using total sampling. Data were collected through direct observation, documentation, and a structured coding sheet comprising likes, comments, shares, saves, follower counts, and content categories. Descriptive statistics and engagement rate calculations were applied to analyze the data. The findings indicate that entertainment and inspirational content generated the highest mean engagement rate at 1.81%, followed by event promotion at 1.63%, educational content at 1.55%, and service information at 0.90%. These results demonstrate that visually appealing, communicative, and emotionally engaging content elicited stronger audience responses than operational service information. This study contributes to the literature on social media engagement in public library communication by identifying content categories associated with higher audience interaction. Practically, public libraries should enhance educational and service-related content through interactive formats, concise captions, and visually attractive presentations. Future research should extend the observation period, incorporate additional Instagram performance metrics, and compare engagement patterns across multiple public library accounts.